2017
DOI: 10.1039/c7ta01057e
|View full text |Cite
|
Sign up to set email alerts
|

A high performance lithium–sulfur battery enabled by a fish-scale porous carbon/sulfur composite and symmetric fluorinated diethoxyethane electrolyte

Abstract: A high performance lithium–sulfur (Li–S) battery comprising a symmetric fluorinated diethoxyethane electrolyte coupled with a fish-scale porous carbon/S composite electrode was demonstrated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
16
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 43 publications
(18 citation statements)
references
References 45 publications
2
16
0
Order By: Relevance
“…The SEM images (Figure S12, Supporting Information) of discharged electrodes in different electrolytes also showed that without the formation of SEI layer, lots of plate‐like structures formed, indicating the dissolution of polysulfides/polyselenides from the carbon host. Similar plate‐like discharge products formation has also been observed in the case of Li/S battery that undergoes severe shuttle effect using DOL/DME‐based electrolytes . While no obvious structure changes can be observed in the HFE‐based electrolytes, confirming bypassed formation of polysulfides/polyselenides via the help of SEI layer.…”
Section: Resultssupporting
confidence: 73%
“…The SEM images (Figure S12, Supporting Information) of discharged electrodes in different electrolytes also showed that without the formation of SEI layer, lots of plate‐like structures formed, indicating the dissolution of polysulfides/polyselenides from the carbon host. Similar plate‐like discharge products formation has also been observed in the case of Li/S battery that undergoes severe shuttle effect using DOL/DME‐based electrolytes . While no obvious structure changes can be observed in the HFE‐based electrolytes, confirming bypassed formation of polysulfides/polyselenides via the help of SEI layer.…”
Section: Resultssupporting
confidence: 73%
“…Yet, another approach, and the one we target here, is to use electrolytes that sparsely dissolve PS e. g . highly concentrated or fluorinated ether‐based electrolytes …”
Section: Figurementioning
confidence: 99%
“…This approach proved to be successful in enhancing the coulombic efficiency of the Li-S batteries. [23][24][25][26][27] Moreover, several groups have indicated the importance of the solvent solvation state in the LiPS dissolution process. [28][29][30] As ar esult, an in-depth understanding of the relationship between LiPS dissolution and the solvation of electrolyte solvents is vital in developing efficient Li-S batteries.…”
mentioning
confidence: 99%